Optimization of University Financial Services Using the Blockchain Technology - Yang, Guixing (Scientific programming, 2022)
At present, the financial work of most colleges and universities is facing the dilemma of low intelligence level. The financial sharing mode of colleges and universities using blockchain technology can effectively supervise their financial management while solving the problems of high costs related to financial sharing services, hidden dangers of data security, and low efficiency. Therefore, this paper makes an in-depth study on the application of blockchain technology and the financial sharing service mode of colleges and universities. Firstly, the University Financial Sharing Service Center platform based on blockchain technology is constructed. Furthermore, each module of the service center platform is described. Combined with the constructed platform, university finance is deeply mined by using the mining algorithm based on certain association rules, which is convenient for effective management. Finally, an artificial intelligence algorithm is used to adaptively optimize financial management. Similarly, the planning model and fitting algorithm of the least square method are used to control the risk of the financial management so as to realize the optimization of the financial sharing service mode. The experiment results demonstrate that the proposed method can effectively improve the efficiency of the financial sharing service and reduce the potential safety problems and costs of financial management.